A Tale of Two States: How State Immigration Climate Affects Belonging to State and Country among Latinos. (23rd May 2018) - Schildkraut, Deborah J; Jiménez, Tomás R; Dovidio, John F; Huo, Yuen J
Abstract: This study assesses the impact of different immigrant policy climates on how Latinos feel about themselves, their place in their state and country, and how they think they are viewed by others. Using survey data from Arizona and New Mexico, we find that Latinos in Arizona exhibit lower levels of belonging than Latinos in New Mexico, but their alienation is confined to the state level. We also find that the U.S. born are most sensitive to the state climate. We conclude that policies that delineate outsiders from insiders by immigration status have wide ranging effects that fall prominently on the U.S. born.